Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Kantor Cabang Bank Mandiri Gunungtua - Rivaldy Amor Naposo Harahap; Daud Arifin; Abdi Setiawan (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the effects of work motivation and work environment on employee performance, with job satisfaction as an intervening variable, among employees of Bank Mandiri Gunungtua Branch Office. A quantitative approach was employed involving 45 respondents, and the data were analyzed using multiple regression and mediation analysis. The results indicate that work motivation does not have a significant effect on employee performance (t = 1.031; Sig. = 0.308). In contrast, the work environment has a positive and significant effect on employee performance (t = 4.856; Sig. = 0.000; B = 1.045). Job satisfaction also shows a positive and significant effect on employee performance, with a path coefficient of 0.742. Furthermore, work motivation (B = 0.217; Sig. = 0.020) and work environment (B = 0.756; Sig. = 0.000) are proven to significantly influence job satisfaction. Sobel test results reveal that job satisfaction significantly mediates the relationship between work environment and employee performance (Z = 2.572). Overall, the findings suggest that improving employee performance is more effectively achieved through optimizing the work environment and strengthening job satisfaction.